Implementasi Pendidikan Karakter Melalui Model Pembelajaran Berbasis Masalah pada Mata Pelajaran PAI di SMP N 2 Purwanegara - Zahra, Unaisatuz; Priyanto, Dwi (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Problem-Based Learning (PBL) is an instructional model that centers on real-world problem solving, aiming to enhance student engagement, foster the development of new knowledge, and create a comfortable and interactive classroom atmosphere. This study aims to describe the implementation of character education through the Problem-Based Learning model in Islamic Religious Education (PAI) at SMP N 2 Purwanegara. The research employed a qualitative approach using a field research method. Data collection techniques included non-participant observation, semi-structured interviews, and documentation. Data analysis was conducted through data reduction, data display, verification, and drawing conclusions, while source triangulation was used to test the validity of the data. The findings revealed that the PBL model was implemented through a structured series of learning activities that encouraged students to think critically and actively engage in solving contextual problems. The teacher functioned as a facilitator, guiding students to analyze, discuss, and present solutions to real-life issues relevant to their experiences. The implementation of PBL proved effective in developing and strengthening students' character traits, such as responsibility, discipline, honesty, and cooperation. The interaction between teachers and students became more interactive and meaningful, resulting in a more dynamic learning environment. Furthermore, students demonstrated a deeper understanding of Islamic Religious Education materials and were able to relate religious values to everyday life. Thus, the Problem-Based Learning model is effective in supporting the reinforcement of character education within the context of Islamic Religious Education in junior high schools.